Feasibility of Jambi Batik-Based Number Pattern Worksheets Integrating Problem Posing and Deep Learning Principles - Intan Juniarmi; Rohati Rohati; Duano Sapta Nusantara; Ade Kumalasari (MASI Mandiri Edukasi, 2026)
Number pattern learning in junior high schools still tends to be procedural, resulting in students being less active and not yet accustomed to posing problems independently. The worksheets commonly used in schools generally contain routine exercises and do not fully support meaningful learning experiences. This study aims to develop and evaluate the feasibility of number pattern student worksheets (LKPD) based on the problem posing model with a deep learning approach integrated with the local cultural context of Jambi batik. The evaluation in this study is limited to validity and practicality aspects. The research employed a development studies type of design research consisting of three stages: preliminary, prototype, and assessment. Data were collected through validation by subject matter and media experts using a Likert-scale instrument, as well as practicality assessments through a limited trial involving one mathematics teacher and six junior high school students. The final validation results showed that the LKPD obtained scores of 64 from the subject matter expert and 61 from the media expert, both categorized as very good. The practicality test results indicated that the LKPD obtained a percentage score of 77.5% from the teacher and 77.29% from students, categorized as very good and good, respectively. These findings indicate that the developed LKPD is valid and practical, making it suitable for use as teaching material in junior high school mathematics learning. In addition, the integration of problem posing, deep learning principles, and Jambi batik context has the potential to support more meaningful learning experiences. This study was limited to validity and practicality testing and did not examine the effectiveness of the worksheets on students’ learning outcomes or analogical reasoning abilities.